Evaluating the Trade Effect of Developing Regional Trade Agreements : A Semi-parametric Approach - Coulibaly, Souleymane (2012)
Many recent papers have pointed to ambiguous trade effects of developing regional trade agreements, calling for a reassessment of their economic merits. This paper focuses on 22 RTAs involving mostly developing countries and covering all the continents and use trade flows over the period 1962-2006. It proposes a two-step estimation approach to assess their trade impact: first estimate a gravity equation excluding the RTA variables, and then use the trade residuals estimated to run a kernel regression for each of the RTAs. This approach allows capturing the non-monotonic trade effects of the RTAs over time while imposing minimal structure on the model, and is flexible enough to be extended to any new RTA. As existing RTAs are deepened and new ones are being negotiated, ensuring that trade creation dominates trade diversion will be essential, particularly in the post-crisis world where resources will be limited for all countries.